Positive Regulation of Spoilage Potential and Biofilm Formation in Shewanella baltica OS155 via Quorum Sensing System Composed of DKP and Orphan LuxRs - Wang, Yanbo; Wang, Feifei; Wang, Chong; Li, Xiuting; Fu, Linglin (Frontiers in Microbiology, 2019)
The spoilage potential and biofilm formation of Shewanella baltica were reported to be regulated by Quorum sensing (QS) system from the phenotype point of view, the specific mechanism is not fully understood. In the present study, the QS autoinducers were detected by UHPLC-MS/MS, cell density-dependent luxR-type genes were obtained through autoregulation experiments among a series of candidates in S. baltica OS155 (SSO). The direct interaction between cyclo-(L-Pro-L-Phe) (PP) and LuxR01 as well as LuxR02 proteins was revealed via binding assay in vitro. Deletion of luxR-type genes (luxR01 and luxR02) impaired spoilage potential and biofilm formation of S. baltica OS155 in various degrees. Transcriptional analysis and qRT-PCR validation showed that spoilage and biofilm-related genes torS, speF and pomA were down-regulated in luxR01 and luxR02 deletion strains. In addition, exogenous PP promoted spoilage potential and biofilm formation, which could be attenuated by luxR01 or luxR02 deletion. Our results revealed an explicit QS system employing PP as autoinducer and two orghan LuxRs as receptors which positively regulated spoilage capacity and biofilm formation via transcriptional regulation of corresponding genes in S. baltica OS155, which provides a specific target for seafood preservation involving QS system.